Enhanced flux-pinning performance of YBCO films derived from a fluorine-free sol-gel process with ceria addition. Issue 2 (1st February 2019) - Lei, Li; Zhang, Zhao; Wang, Xiuting; Zhao, Gaoyang; Jia, Jiqiang; Duan, Zongfan; Li, Ying; Jin, Lihua; Li, Chengshan; Zhang, Pingxiang
Abstract: In this work, a facile and effective method which can significantly improve the flux-pinning performance of YBCO films was reported. YBCO/CeO2 composite films were prepared on LaAlO3 (LAO) single crystal substrates through a fluorine-free sol-gel approach with a certain amount of ceria addition. During the nucleation and growth of YBCO films, CeO2 reacted with the barium-contained phase in YBCO precursors to generate the nanosized BaCeO3 phase and thus the redundant Y2 O3 and CuO phases remained, leading to the wrong stacking of Cu atoms to form the stacking faults of Cu-O planes, which has been demonstrated by XRD, TEM, SEM and EDS results. The variation of critical current density ( J c ) and flux-pinning force ( F p ) with the percentage of ceria addition was investigated, and the results show that YBCO film with the amount of 5 mol% of ceria addition exhibits the highest J c and the strongest F p at the same temperature and applied magnetic fields. In addition, the stacking faults effectively reduced the degree of dependency of J c of YBCO film on the applied magnetic field especially at low temperature.